Occult fractures of the proximal femur: imaging diagnosis and management of 82 cases in a regional trauma center. Issue 1 (December 2015) - Deleanu, Bogdan; Prejbeanu, Radu; Tsiridis, Eleftherios; Vermesan, Dinu; Crisan, Dan; Haragus, Horia; Predescu, Vlad; Birsasteanu, Florin
Abstract Background Occult hip fractures are often difficult to identify in busy trauma units. We aimed to present our institutions experience in the diagnosis and treatment of occult fractures around the hip and to help define a clinical and radiological management algorithm. Method We conducted a seven-year retrospective hospital medical record analysis. The electronic database was searched for ICD-10 CM codes S72.0 and S72.1 used for proximal femoral fractures upon patient discharge. We identified 34 (4.83 %) femoral neck fractures and 48 (4.42 %) trochanteric fractures labeled as occult. Results The majority of the cases were diagnosed by primary MRI scan (57.4 %) and 12 were diagnosed by emergency CT scan (14.6 %). For the remaining cases the final diagnosis was confirmed by 72 h CT scan in 9 patients (representing 39 % of the false negative cases) or by MRI in the rest of 14 patients. MRI was best at detecting incomplete pertrochanteric fracture patterns (13.45 % of total) and incomplete fractures of the greater trochanter (3.65 % of total) respectively. It also detected the majority of Garden I femoral neck fractures (20.7 % of total). CT scanning accurately detected 100 % of Garden 2 fractures (2.44 %) and 25 % (3.65 %) of the complete pertrochanteric fractures (false negative 25 %). Conclusion Occult fractures should be suspected in all patients with traumatic onset of hip pain that is inconsistent with normal radiographic findings. MRI is the golden standard but not as readily available not as cheap and not quite as quick to perform as as a CT scan. The latter which in turn can provide falsely negative results in the first 24 h. Improved imaging protocols could expedite management and improve treatment.